ANALYSIS OF THE ESP LIFE TIME WITH THE APPLICATION OF POISSON DISTRIBUTION METHOD IN FIELD X - JATI (NIM : 12299022), NUGROHO
Electric Submersible Pump (ESP) is one of the most regular artificial lift pump used as artificial lift pump in petroleum world. The application of this method is very large, it is considered that more than quarter of worldÃ‚Â’s petroleum production is produced with the help from this method. Analysis of ESP operation becomes so important, one that should be considered is about reliability that have connection with failures and life time of an ESP unit. Analysis of ESP operation is very important for economic calculation and production planning. Poisson distribution is one of diskret distribution method which often used to describe reliability matters of an equipment or to examine a life testing of a component. The advantages of Poisson distribution is that this method is very simple but had accuracy as good as other distribution, beside that, this method only need a single random variable and has a single parameter which has a large application to solve any problem that occur. This study evaluate ESP life time as a single random variable and applied the single parameter from Poisson distribution to analyze installation of ESP unit. The evaluation is to define the expected life and perform installation efficiency analysis of ESP unit in one field. The last is comparing the result of ESP operation analysis used Poisson method and analysis used Weibull method, so we can figure advantage and disadvantage between each methods.